A Specialized Ceramic Assemblage for Water Pulling The Middle Chalcolithic Well of Tel Tsaf, Israel - Streit, Katharina; Garfinḳel, Yosef 1956- (2015)
The authors explore aspects of a well uncovered at Tel Tsaf, Israel, dating to the Middle Chal-colithic Period, ca. 4800 cal B.C. The well was uncovered in close proximity to the settlement of Tel Tsaf, shedding light on the hydraulic technology of the community. An exceptionally rich assemblage of complete vessels has been found in situ at the bottom of the shaft. The ceramics show two distinct typological features uncommon to other assemblages of the Middle Chalcolithic: double paired handles and the so-called beakers, a new ceramic shape dominant in this assemblage. We argue that the ceramic assemblage comprises task-specific vessel shapes designed for drawing water from a well. The examples from Tel Tsaf are currently the earliest of their kind.
Keywords: BEAKERS (Tableware); Ceramics; COPPER Age pottery; Middle Chalcolithic; SHAFTS (Excavations); Technology; Ceramics; Radiocarbon dating; Southern Levant; Wells